2014
DOI: 10.1523/jneurosci.3187-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Windows in Visual Processing: “Prestimulus Brain State” and “Poststimulus Phase Reset” Segregate Visual Transients on Different Temporal Scales

Abstract: Dynamic vision requires both stability of the current perceptual representation and sensitivity to the accumulation of sensory evidence over time. Here we study the electrophysiological signatures of this intricate balance between temporal segregation and integration in vision. Within a forward masking paradigm with short and long stimulus onset asynchronies (SOA), we manipulated the temporal overlap of the visual persistence of two successive transients. Human observers enumerated the items presented in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
51
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 74 publications
12
51
2
Order By: Relevance
“…This frequency range has been implicated in detection of nearthreshold stimuli (particularly oscillations in the alpha range: Busch, Dubois, & VanRullen, 2009;Mathewson, Beck, Fabiani, Ro, & Gratton, 2011;VanRullen, Busch, Drewes, & Dubois, 2011), in oscillations in spatial attention (low alpha or high theta: Fiebelkorn et al, 2011;Fiebelkorn, Saalmann, & Kastner, 2013;Landau & Fries, 2012;Song, Meng, Chen, Zhou, & Luo, 2014), and in recurrent processing (theta: Drewes, Zhu, Wutz, & Melcher, 2015;Wutz, Muschter, van Koningsbruggen, & Melcher, 2014;Wutz, Weisz, Braun, & Melcher, 2014). On the one hand, theta (5-7 Hz) has been implicated in many tasks involving image categorization or binding features to specific objects or locations (Drewes et al, 2015;Wutz, Weisz, et al, 2014;. Higher frequencies, in the alpha band, have been implicated in the temporal resolution of perception (Cecere, Rees, & Romei, 2015;Cravo et al, 2015;Gho & Varela, 1988;Milton & Pleydell, 2016;Samaha & Postle, 2015;Varela et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…This frequency range has been implicated in detection of nearthreshold stimuli (particularly oscillations in the alpha range: Busch, Dubois, & VanRullen, 2009;Mathewson, Beck, Fabiani, Ro, & Gratton, 2011;VanRullen, Busch, Drewes, & Dubois, 2011), in oscillations in spatial attention (low alpha or high theta: Fiebelkorn et al, 2011;Fiebelkorn, Saalmann, & Kastner, 2013;Landau & Fries, 2012;Song, Meng, Chen, Zhou, & Luo, 2014), and in recurrent processing (theta: Drewes, Zhu, Wutz, & Melcher, 2015;Wutz, Muschter, van Koningsbruggen, & Melcher, 2014;Wutz, Weisz, Braun, & Melcher, 2014). On the one hand, theta (5-7 Hz) has been implicated in many tasks involving image categorization or binding features to specific objects or locations (Drewes et al, 2015;Wutz, Weisz, et al, 2014;. Higher frequencies, in the alpha band, have been implicated in the temporal resolution of perception (Cecere, Rees, & Romei, 2015;Cravo et al, 2015;Gho & Varela, 1988;Milton & Pleydell, 2016;Samaha & Postle, 2015;Varela et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Segregating sensory changes exceeding this critical time frame (long SOA trials) instead depends on slower beta power modulations prior to stimulus onset (Wutz et al, 2014). The time course of the alpha phase synchrony reset (≈100 ms; ≈one alpha cycle) is consistent with the perceptual effects of integration masking (Enns and Di Lollo, 2000; Breitmeyer and Öğmen, 2006; Wutz et al, 2012).…”
Section: Neural Mechanisms: Alpha Phase Synchronizes Individuation Anmentioning
confidence: 99%
“…visual perception | temporal integration | alpha oscillations | oscillation frequency | top-down control V isual perception is tasked both with constructing stable representations over time as well as maximizing sensitivity to transient changes. A large body of work has shown that neural oscillations in the alpha band (8)(9)(10)(11)(12) are partially responsible for determining the temporal resolution of perception, such that when discrete events occur within the same oscillatory cycle they can become perceptually integrated (1)(2)(3)(4)(5)(6)(7)(8). For instance, individuals with higher peak alpha frequencies have perception with higher temporal resolution (2,9), indicating that lower peak frequencies correspond to integration over longer time windows.…”
mentioning
confidence: 99%